Challenges Faced by Health Center Nurses in the Implementation of Electronic Nursing Care (ENC): Qualitative Descriptive Analysis in City X - Azmi, Nadila Nur (Fakultas Ilmu Kesehatan Universitas Gresik, 2024)
The implementation of Electronic Nursing Care (ENC) as part of the digital transformation of health in health centers faces various obstacles that need to be identified to ensure its success and sustainability. This study aims to identify and analyze challenges in the implementation of ENC in the City X Health Center and formulate strategic recommendations to overcome them. This descriptive qualitative research used purposive and snowball sampling techniques to recruit 15 nurses from various health centers. Data was collected through in-depth interviews, participant observations, and document reviews, then analyzed using thematic analysis. The research reveals three main challenge themes: (1) Technical and infrastructure challenges (unstable internet connectivity, limited hardware, system frequent errors); (2) HR challenges (digital competency gap, inadequate training, resistance to change, double workload); (3) Organizational challenges (suboptimal management support, unclear policies, limited technical support). These challenges have an impact on reducing service quality and increasing the workload of nurses. The implementation of ENC at the City X Health Center faces multidimensional obstacles that are interrelated. A comprehensive approach that includes infrastructure improvements, human resource capacity building, and strengthening organizational support is needed to ensure the success of digital transformation in the primary health sector.